Dog lost - Lee, Ingrid, 1948- (Chicken House, 2008)
After living happily in a warm home with an eleven-year-old boy, a pit bull terrier loses his owner and is forced to survive on the streets, where its brave deeds surprise many residents who dislike or fear pit bulls.